Procalcitonin as a biomarker for postoperative pneumonia: a study on dynamics following cardiopulmonary bypass in adults - Guang-Xu Mao; Li-Yun Wang; Wen-Sen Chen; Sheng Zhao; Yong-Feng Shao; Yu-Zhen Guan; Zhen Lu; Feng Zang (BMC Cardiovascular Disorders)
Abstract Objective Postoperative pneumonia (POP) frequently complicates cardiac surgery that involves cardiopulmonary bypass (CPB). This study aimed to assess the diagnostic utility of procalcitonin (PCT) for identifying pneumonia after CPB-assisted cardiac surgery. Methods Patients diagnosed with POP were enrolled in the retrospective matched case-control study and were admitted to a Grade III general hospital in Nanjing in 2023. POP diagnosis was determined based on a combination of clinical and microbiological criteria.PCT and white blood cell count (WBC) data were systematically collected from day 1 (T1) to day 5 (T5). Receiver operating characteristic (ROC) curve analysis and subject operating characteristics were utilized to evaluate the diagnostic performance of biomarkers. At the same time, a binary logistic regression model was developed to identify factors that influence the diagnosis of POP. Results The study included 220 age- and sex-matched patients, comprising 56 individuals with POP and 164 uninfected patients constituting the non-POP group. ROC curve analysis revealed that serum PCT concentration exhibited an AUC > 0.7 from day 2 to day 5, whereas other indices demonstrated AUCs < 0.7 at these time points. Univariate and multivariate analyses highlighted serum PCT concentration on day 2, WBC count on day 5, the PCTT4-T1 variation rate, and days of mechanical ventilation as significant predictive factors for POP diagnosis, each demonstrating statistical significance (P < 0.05). The calculated AUC was 0.837 (95%CI: 0.773–0.902). The absolute PCT value exhibited superior diagnostic performance relative to its variance rate and WBC count, yielding optimal diagnostic accuracy with a cutoff value of 3.45 ng/ml. Conclusion Serum PCT absolute value demonstrates higher sensitivity and specificity than other indices, offering superior diagnostic potential for predicting POP.